CPW-Fed Fractal Slot Antenna for UWB Application - Hou Zhang; Hai-Yang Xu; Bo Tian; Xian-Feng Zeng (International Journal of Antennas and Propagation)
A novel printed ultrawideband (UWB) CPW-fed Koch fractal slot antenna is proposed. The UWB bandwidth is largely enhanced by the three-iteration Koch fractal slot whose extrusive angle is 900 instead of 600 to obtain better convoluted shape and self-similarity. The −10 dB impedance bandwidth is 3400 MHz (1270–4670 MHz) or about 114% in comparison with 1290 MHz (1620–2910 MHz) or about 57% of the referenced square slot antenna. Details of the proposed antenna design and performance are presented and discussed.